ALOX5AP Variants are Associated with In-Stent Restenosis After Percutaneous Coronary Intervention - Shah, Svati H. (2008)
BACKGROUND: Use of drug-eluting stents (DES) has reduced in-stent restenosis after percutaneous coronary intervention (PCI); however, DES are associated with late stent thrombosis. There is no accurate way to predict in-stent restenosis, although risk factors for atherosclerosis overlap those for in-stent restenosis. Therefore, we evaluated atherosclerosis candidate genes for association with in-stent restenosis. METHODS: We identified 46 consecutive cases that had undergone PCI with bare-metal stents who subsequently developed symptomatic in-stent restenosis of the target lesion (≥75% luminal narrowing) within six months. Forty-six age-, race-, vessel-diameter- and sex-matched controls without in-stent restenosis after PCI with bare-metal stent were also identified. Single-nucleotide polymorphisms (SNPs, N=82) from 39 candidate atherosclerosis genes were genotyped. Multivariable logistic regression models were used to test for association. RESULTS: Five SNPs were associated with in-stent restenosis. Three ALOX5AP SNPs were most strongly associated, two with increased risk (OR 3.74, p=0.01; OR 3.46, p=0.02), and the third with decreased risk of in-stent restenosis (OR 0.09, p=0.004). Two ALOX5AP haplotypes were associated with in-stent restenosis (HapB: OR 3.13, p=0.03); and a haplotype similar to HapA: OR 0.14, p=0.0009). CONCLUSIONS: ALOX5AP, a gene within the inflammatory leukotriene pathway linked to and associated with coronary atherosclerosis, is also associated with in-stent restenosis. Genotyping these variants may help identify those at risk for in-stent restenosis who would benefit most from use of DES.